Application of atom probe tomography in understanding high entropy alloys: 3D local chemical compositions in atomic scale analysis. (April 2021) - Hu, Rong; Jin, Shenbao; Sha, Gang
Abstract: High-entropy alloys (HEAs), also called multi-principal-elements alloys, possess extraordinary mechanical properties, including high strength and hardness, thermal stability, corrosion resistance and radiation resistance, due to their unique and complex microstructures. The comprehensive understanding of their microstructures down to atomic level plays a vital role in developing HEAs, for tuning manufacturing parameters, examining their phase stabilities under severe conditions for future applications, and determining origins of their excellent mechanical properties. The expansion of the fundamental knowledge of the microstructure strongly relies on the advance of high-resolution analytical techniques. As a state-of-the-art technique, atom probe tomography (APT), with a high spatial resolution and ability in detecting individual atoms, has emerged as an important tool in studying HEAs. Herein, an effort is made to review the recent application of APT in understanding HEAs. It begins with the experimental approaches in using APT to reveal atomic-scale structural and chemical information of HEAs, and follows by typical applications of APT in high-performance HEAs processed by different routes, understanding their microstructural stability, and structure–property relationships. Finally, major challenges and perspectives in APT applications to address fundamental science of HEAs are discussed.